Ownership and use of insecticide-treated nets in Myanmar: insights from a nationally representative demographic and health survey - Kyawt Mon Win; Kyaw Lwin Show; Jetsumon Sattabongkot; Pyae Linn Aung (Malaria Journal, 2024)
Abstract Background Malaria poses a substantial public health threat in Myanmar, indicating the need for rigorous efforts to achieve elimination of the disease nationwide by 2030. The use of insecticide-treated nets (ITNs) forms part of a pivotal strategy for preventing transmission. This study explored the ownership and use of ITNs in Myanmar and identified factors associated with non-use of ITNs. Methods Household datasets from the 2015–2016 Myanmar Demographic and Health Survey were utilised, which encompassed all household members except children under the age of five. Descriptive statistics and inferential tests, including simple and multiple logistics regression models and Pearson correlations, were employed for analysis. All analyses, taking the two-stage stratified cluster sampling design into account, used weighting factors and the “svyset” command in STATA. The ownership and use of bed nets were also visualised in QGIS maps. Results Among the 46,507 participants, 22.3% (95% CI 20.0%, 24.5%) had access to ITNs, with only 15.3% (95% CI 13.7, 17.1%) sleeping under an ITN the night before the survey. Factors associated with the non-use of ITNs included age category (15–34 years—aOR: 1.17, 95% CI 1.01, 1.30; 50+ years—aOR: 1.19, 95% CI 1.06, 1.33), location (delta or lowland—aOR: 5.39, 95% CI 3.94, 7.38; hills—aOR: 1.80, 95% CI 1.20, 2.71; plains—aOR: 3.89, 95% CI 2.51, 6.03), urban residency (aOR: 1.63, 95% CI 1.22, 2.17), and wealth quintile (third—aOR: 1.38, 95% CI 1.08, 1.75; fourth—aOR: 1.65, 95% CI 1.23, 2.23; fifth—aOR: 1.47, 95% CI 1.02, 2.13). A coherent distribution of the ownership and use of ITNs was seen across all states/regions, and a strong correlation existed between the ownership and use of ITNs (r: 0.9795, 95% CI 0.9377, 0.9933, alpha < 0.001). Conclusions This study identified relatively low percentages of ITN ownership and use, indicating the need to increase the distribution of ITNs to achieve the target of at least one ITN per every two people. Strengthening the use of ITNs ...